1991
DOI: 10.1177/00220345910700110401
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic-force Characteristics in the Assessment of Oral Function

Abstract: The purpose of this investigation was to examine the utility of EMG-force characteristics as reliable and valid parameters by which to assess oral function. Masseter-muscle activity was recorded during controlled isometric biting exercises performed at various bite openings and force levels on two separate occasions. Measured muscle-activity levels, as well as the EMG-force characteristics of slope and y-intercept, were compared between bite openings and experimental trials. Sensitivity, assessed as the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 20 publications
2
24
1
1
Order By: Relevance
“…ings of the current study and some previous work. 11,18 The difference between the results in the current study and the findings of Mao and Osborn 20 may relate to the different methodologies used; a ramp force in the current study and incremental 50-N bite tasks in their study. Furthermore, neither van Eidjen et al 33 nor Mao and Osborn 20 investigated the first 50 N of bite force; the current study showed that many of the masseter SMUs were recruited in this part of the contraction.…”
Section: Variability In the Contribution Of Muscles To Jawcontrasting
confidence: 70%
“…ings of the current study and some previous work. 11,18 The difference between the results in the current study and the findings of Mao and Osborn 20 may relate to the different methodologies used; a ramp force in the current study and incremental 50-N bite tasks in their study. Furthermore, neither van Eidjen et al 33 nor Mao and Osborn 20 investigated the first 50 N of bite force; the current study showed that many of the masseter SMUs were recruited in this part of the contraction.…”
Section: Variability In the Contribution Of Muscles To Jawcontrasting
confidence: 70%
“…A previous study has shown large variability of EMG activity exhibited between subjects although they performed identical tasks [24]. In the present study, there was a marginal difference of EMG activity within the same site during an identical task.…”
Section: Submaximal Contractions Using Emg Feedback From Anterior Temsupporting
confidence: 57%
“…This proposal has been rejected by several recent studies that have examined the relationship between maximal biting force and experimental variations in OVD. As the OVD is increased from a position of infra-gnathism (Morimoto et al, 1996) to a position 15 to 20 mm greater than the free-way space norm, the maximal biting force also increases (Boucher et al, 1959;Manns et al, 1979;Mackenna and Turker, 1983;Fields et al, 1986;Lindauer et al, 1991;Prombonas et al, 1994) (Fig. ).…”
Section: (112) Effects Of a Modification Of Head Position On The Antmentioning
confidence: 98%